DIGITAL CONNECTIVITY AND MIGRATION IN THE INTERNATIONALIZATION OF INDONESIAN LANGUAGE - Refi Riduan Achmad; Hasan, Nabila Aulia (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
The development of digital technology and global mobility has created new opportunities for the Indonesian language to play a role as a language of international communication. Through the phenomena of migration and the development of social media, Indonesian is not only used by native speakers but is also beginning to be learned and utilized by the global community. This study aims to analyze the potential of Indonesian as a global language, emphasizing migration trends and digital connectivity in 2025. The methods applied are literature review and content analysis of Indonesian-language digital media reaching international audiences. The results indicate that Indonesian is appealing due to its expressive, communicative nature and its ability to adapt to technology, particularly on platforms like YouTube, TikTok, and language learning applications. However, challenges remain, such as the mastery of foreign languages, the lack of internationalization policies for the language, and limited support for local language technology. This study proposes strategies for the conservation and development of Indonesian through cultural diplomacy, strengthening language technology, and integration into global curricula. With effective strategies, Indonesian has the opportunity to become one of the important global languages in the age of digital connectivity. Keyword: Indonesian Language Internationalization, Digital Connectivity, Global Migration